Imperative Of Research Output and Evidence-Based in Policy Formulation in Nigeria: A Catalyst to National Development - Samson Olukayode Bamidele (Eastasouth Institute, 2026)
The impact of research outcomes and evidence-based in policy making process in every political system cannot be underestimated, as it serves as veritable instrument in accurate and result oriented policies, especially in the developed countries. However, evidence-based research has been the agitation of academics and policy makers over the years. In Nigeria, this practice is so unpopular because its lack of political will of leaders and apparent gap between researchers, research informed outcomes and policy makers. Whereas, the socio-economic and technical challenges of the society usually transform to political agenda of government, evidence-based research often play major role. The study uses secondary data to highlight the imperative of research output and evidence-informed outcome in policy making. And conclude that if Nigeria embrace this, it will bring optima and successful development policies in the country.